Psychometric properties of the Child Oral Impacts on Daily Performances (C-OIDP) index: a cross-sectional and an intervention study of adolescents in Bosnia and Herzegovina - Jelena Erić; Ljiljana Bjelović; Svjetlana Janković; Bojana Davidović; Djordje Bozović; Jelena Krunić (BMC, 2023)
Abstract Background The clinical measures are not sufficient to assess oral health because they don't tell us anything about functional and psychosocial aspects of oral health and do not reflect person's concerns and subjectively perceived symptoms. This study aimed to investigate the validity, reliability and responsiveness of the child Oral Impacts on Daily Performances (C-OIDP) index among Bosnian 12-14 years old schoolchildren. Methods The study population comprised 203 primary schoolchildren aged 12-14 years attending three schools in the eastern part of Bosnia and Herzegovina. Data were collected through: a clinical oral examination, oral health questionnaire and C-OIDP questionnaire. The validity and reliability of the C-OIDP were tested on a sample of 203 school-going children while responsiveness of the C-OIDP was assessed on 42 randomly chosen participants requiring a dental treatment. Results In terms of reliability, Cronbach's alpha coefficient and the intraclass correlation coefficient were 0.86 and 0.85, respectively. Regarding the testing of construct validity, the C-OIDP score was increased as children's self-reported oral health changed from excellent to very bad and from very satisfied to dissatisfied. There was a significant improvement in C-OIDP post-treatment score compared with C-OIDP pre-treatment score. Overall, 63.4% of participants reported at least one oral impact in the last 3 months. The most affected performances were "eating" (38.4%) and "speaking" (25.1%). Conclusion The Bosnian version of the C-OIDP showed satisfactory validity, reliability and responsiveness and can be used as an appropriate OHRQoL measure for further epidemiological researches.